Strukturmikro, Kekerasan, dan Ketahanan Korosi Baja Tahan Karat Martensitik 13Cr3Mo3Ni Hasil Quench-Temper dengan Variasi Temperatur dan Waktu Austenisasi [Microstructure, Hardness, and Corrosion Resistant of Martensitic Stainless Steel 13Cr3Mo3Ni after Quench-Temper with Various Austenization Temperature and Time] - Siska Prifiharni; Denni Ahmad; Andini Juniarsih; Efendi Mabruri (National Research and Innovation Agency (BRIN), 2017)
Martensitic stainless steel type 410 have been extensively used for turbine blade in steam turbine system. Their properties can be improved in various ways, such as modification element and heat treatment. The modified stainless steel in this case is martensitic stainless steel 13Cr-3Mo-3Ni were hot forged then annealed. Afterwards, martensitic stainless steel 13Cr-3Mo-3Ni were prepared and heat treated. Martensitic stainless steel 13Cr-3Mo-3Ni were austenized at temperature 950, 1000, 1050, dan 1100 °C for 1 and 3 hour followed by quench in oil. After quenching, material were tempered at 650°C for 1 hour. Several examinations were carried out on the material such as of hardness test with rockwell C, metallographic using optical microscope, and corrosion test using CMS (corrosion measurement system). The results show that martensitic stainless steel 13Cr3Mo3Ni at austenitizing temperature of 950 °C for 1 hour and tempering at 650 °C for 1 hour has the lowest hardness value with hardness value was 33.5 HRC and the lowest corrosion rate 0.02 mpy, whereas at austenitizing temperature of 1100 °C for 3 hours and tempering at 650 °C for 1 hour has the highest hardness value with hardness value was 46.2 HRC and the highest corrosion rate 1.62 mpy. The microstructures formed are martensite, carbide, and ferrite delta phases. Increased hardness at austenitizing temperature 1100 °C is due to an increase in carbide content in the martensite phase. However, carbide precipitation formed during quenching process can decrease corrosion resistance as Cr and Mo levels decrease in carbides.AbstrakBaja tahan karat martensitik tipe 410 biasa digunakan untuk aplikasi sudu turbin pada steam turbine. Perilaku baja tahan karat jenis ini dapat diperbaiki dengan berbagai cara, salah satunya yaitu dengan cara memodifikasi unsur baja tahan karat tipe 410 tersebut dan perlakuan panas. Baja tahan karat yang telah dimodifikasi dilakukan proses hot forging kemudian dianil. Sampel kemudian dipreparasi dan dilakukan proses perlakuan panas. Proses perlakuan panas yang dilakukan yaitu austenitisasi pada variasi suhu 950, 1000, 1050, dan 1100⁰C selama 1 dan 3 jam dan didinginkan dengan menggunakan media oli. Sampel yang telah diaustenitiasi dilakukan proses temper pada suhu 650⁰C selama 1 jam. Sampel tersebut kemudian dilakukan uji kekerasan, strukturmikro, dan ketahanan korosi yang terjadi setelah melalui proses perlakuan panas. Hasil menunjukkan bahwa nilai kekerasan dan laju korosi yang paling rendah pada suhu austenitisasi 950⁰C selama 1 jam dan paling tinggi pada suhu austenitisasi 1100⁰C selama 3 jam. Hal ini dapat terjadi karena adanya perubahan struktur martensit yang menjadi lebih kasar pada suhu austenitisasi yang lebih tinggi.